EFFECTS OF ORGANIC FERTILIZATION ON COTTON (GOSSYPIUM HIRSUTUM) CROP - Díaz-Gutiérrez, Jean Pierre (2023)
Cotton is a very demanding plant at a nutritional level; for this reason, it is necessary to carry out an effective application of fertilizers, standing out in recent times as those of organic origin. The main of this research was to evaluate, through a literature review, the importance of organic fertilization in the sustainable production of cotton cultivation. It was used in the study of 44 scientific documents from the Scielo, Redalyc, Latindex, and Scopus databases. The search for scientific manuscripts was comprised in the period between 2002 and 2022, using keywords in both Spanish and English: ¨cotton¨, ¨origin of cotton¨, ¨cotton distribution¨, ¨benefits and uses of cotton cultivation¨, ¨vegetative cycle of cotton¨, ¨cotton phenology¨, ¨effects of organic fertilization in cotton cultivation¨.¨nutritional requirements of cotton cultivation¨, ¨mineral and organic fertilization of cotton cultivation¨, ¨effects of organic fertilization on cotton production growth¨. The organic fertilization carried out in several studies has agreed that it is possible to produce cotton with fertilizers of organic origin (bovine manure, pig manure, guano, chicken manure, humus, etc.). In addition, the importance of the decrease in production costs and the contribution to the improvement of the physical properties of the soil by helping to retain more significant moisture due to the high concentration of organic matter.